2022
DOI: 10.1088/1755-1315/967/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Potential various mangrove fruit extract as a bacterial growth resistor in Euthynnus affinis

Abstract: This research study effect of various mangrove fruit submersion as a bacterial growth resistor is in Euthynnus affinis in the process of preserving the fish. The designed used in this research was with theexperimental design using 4 treatments (Avicennia sp., Sonneratia sp., and Bruguierra sp.) mangrove extract with submersion fruit: water (3:1). The parameters being observed included the organoleptic test, total plate count number test, pH test, moisture content and protein content. The result of the study sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…The amount of carbohydrates, protein, and fat in Mangrove fruit ranges from 10 to 500 mg/g (Budiyanto et al, 2022). The use of Mangrove fruit from the study by Harahap et al (2022) found that Mangroves inhibit bacterial growth. This is contrary to the composition of Mangrove, which contains components that support bacterial growth.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of carbohydrates, protein, and fat in Mangrove fruit ranges from 10 to 500 mg/g (Budiyanto et al, 2022). The use of Mangrove fruit from the study by Harahap et al (2022) found that Mangroves inhibit bacterial growth. This is contrary to the composition of Mangrove, which contains components that support bacterial growth.…”
Section: Introductionmentioning
confidence: 99%